2006
DOI: 10.1128/jb.00104-06
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of theHelicobacter pyloriFe-S Cluster Synthesis Protein NifS by Iron, Oxidative Stress Conditions, and Fur

Abstract: Transcription of both chromosomal and extrachromosomally introduced nifS was regulated (up-expressed) by oxygen or by supplemental iron conditions. This up-expression was not observed in a fur mutant strain background or when an iron chelator was added. Iron-bound Fur (but not apo-Fur) recognized the nifS promoter, and Fur bound significantly farther upstream (؊155 bp to ؊190 bp and ؊210 to ؊240 bp) in the promoter than documented Helicobacter pylori Fur binding regions. This binding was stronger than Fur reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 25 publications
1
33
0
1
Order By: Relevance
“…Specifically, stress-related Leptospirillum group II proteins more abundant in the laboratory biofilms included the iron-sulfur cluster assembly proteins, which form the center of many important redox active enzymes (Supplementary Table 5). It has been suggested that upregulation of the iron-sulfur cluster assembly operon occurs during periods of oxidative stress in response to free radical damage to the redox active sites of iron-sulfur proteins (Alamuri et al, 2006). Furthermore, a separate abundant oxidative stress protein in the laboratory sample, peptide methionine sulfoxide reductase, has been shown to have a direct role in protection from reactive oxygen species (Moskovitz et al, 1995).…”
Section: Acid Mine Drainage Chemoautotrophic Productionmentioning
confidence: 99%
“…Specifically, stress-related Leptospirillum group II proteins more abundant in the laboratory biofilms included the iron-sulfur cluster assembly proteins, which form the center of many important redox active enzymes (Supplementary Table 5). It has been suggested that upregulation of the iron-sulfur cluster assembly operon occurs during periods of oxidative stress in response to free radical damage to the redox active sites of iron-sulfur proteins (Alamuri et al, 2006). Furthermore, a separate abundant oxidative stress protein in the laboratory sample, peptide methionine sulfoxide reductase, has been shown to have a direct role in protection from reactive oxygen species (Moskovitz et al, 1995).…”
Section: Acid Mine Drainage Chemoautotrophic Productionmentioning
confidence: 99%
“…H. pylori responds and adapts to gastric stressors by altering gene expression through the use of transcriptional regulators. One such regulator, the ferric uptake regulator (Fur), is utilized to maintain iron homeostasis (4-6) but also to respond to pH (7)(8)(9), nitrosative, and oxidative stressors (10)(11)(12). Given the paucity of transcriptional regulators found in H. pylori compared to other bacterial organisms (13), it is perhaps not surprising that through the course of evolution, H. pylori Fur has taken on a more global role in gene regulation beyond iron uptake and storage.…”
mentioning
confidence: 99%
“…In addition, it is also currently unclear whether apo-Fur functions as an oligomer (similar to Fe 2ϩ -Fur) or whether an alternative form of the protein is required for this type of regulation. Moreover, direct Fe 2ϩ -Fur-mediated activation has been demonstrated definitively for only one gene (nifS) in H. pylori, and the possible mechanisms underlying activation have not been determined (6). Given the distal location of the Fur binding sites in H. pylori Fe 2ϩ -Fur-activated promoters (6,197), it is not intuitively clear whether or not Fur would be able to interact directly with RNAP or whether another factor is involved in facilitating activation.…”
Section: Discussionmentioning
confidence: 99%
“…Detailed analysis of Fur regulation of the nifS promoter suggests that Fur can in fact act as a transcriptional activator. Under iron-replete conditions, Fur was found to protect two distinct regions within the nifS promoter (6). Although there are no clear Fur boxes in the nifS promoter, the Fur binding regions were reported to be 150 and 200 nucleotides upstream from the transcriptional start, which could be consistent with an orientation of Fur needed to activate transcription.…”
Section: Vol 75 2011 Variations In Mechanisms Of Epsilonproteobactementioning
confidence: 92%
See 1 more Smart Citation